Insights into the structures and properties of dyes in the Fenton catalytic process for treating wastewater effluent - Pervez, Md. Nahid; Mishu, Mst. Monira Rahman; Tanvir, Naim Pervez; Talukder, Md Eman; Cai, Yingjie; Telegin, Felix Y.; Zhao, Yaping; Naddeo, Vincenzo (Water environment research, 2023)
A notable level of apprehension exists over the adverse impacts of dye pollution on aquatic ecosystems and human well‐being. The primary objective of this research is to assess the effectiveness of Fenton catalytic reactions in degrading 14 different commercial azo dyes (both single and double) present in aqueous solutions. The investigation focused on the function of dye structures, using a combination of experimental data and examination of theoretical factors. Dye degradation process was carried out at pH 3, and the concentrations of Fe2+ (10−4 mol/L), H2O2 (2 × 10−3 mol/L), and dye (0.05 g/L). The findings revealed that dyes with a larger molecular weight were more effective at degrading (D%), with the overall degradation efficiency varying from 0% to 94%. Functional groups played an important role in degradation efficiency; for example, dyes with higher aromatic rings led to less D%, while a higher number of sulfonic, methyl, and nitro groups was responsible for better D%. Notably, the presence of OH groups in the backbone of dyes (AB 24, ABE 113, and MB 9) formed the Fe complex during the catalytic process, and the D% was minimal. On the other hand, theoretical quantum calculations such as the greater the JCLogP, highest occupied molecular orbital, and Dipole moment value, the higher the degradation efficiency. And dyes with low lowest unoccupied molecular orbital tended to have a better degradation efficiency. To some extent, UV–Vis spectral analysis was investigated to determine the degradation pathway, and the pseudo‐second‐order kinetic model fitted better in the degradation process. The overall experimental and theoretical findings suggested that dye degradation efficiency by the Fenton process is structure‐dependent. Practitioner Points Insights into the role of azo dye structures‐properties on degradation efficiency. Higher molecular weight and sulfonic groups containing dyes showed better degradation efficiency. Hydroxyl groups play the formation of the Fe complex during the degradation process. Higher values of HOMO and lower values of LUMO enhanced degradation efficiency. The pseudo‐second‐order (PSO) kinetic model obeyed the Fenton process. Influence of dye structures in the Fenton catalytic process for treating wastewater.